2009
DOI: 10.1007/s11695-009-9933-4
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Fully Stapled Laparoscopic Roux-en-Y Gastric Bypass for Obesity Reduces Early Immediate Postoperative Morbidity and Mortality: A Single Center Study on 2606 Patients

Abstract: Background Various techniques of laparoscopic Roux-en-Y gastric bypass have been described. We completely standardized this procedure to minimize its sometimes substantial morbidity and mortality. This study describes our experience with the standardized fully stapled laparoscopic Roux-en-Y gastric bypass (FS-LRYGB) and its influence on the 30-day morbidity and mortality.Methods We retrospectively analyzed 2,645 patients who underwent FS-LRYGB from May 2004 to August 2008. Operative time, hospital stay and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 43 publications
6
41
1
1
Order By: Relevance
“…We had 56 (2.8%) early complications occurring in 48 patients, including ten anastomotic leakages (0.50%). Our early complication rate is acceptable and comparable with good results from other high-volume units [14,[19][20][21]. Our re-operation rate was 1.3%, but some of the leaks and bleedings could probably have been treated conservatively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We had 56 (2.8%) early complications occurring in 48 patients, including ten anastomotic leakages (0.50%). Our early complication rate is acceptable and comparable with good results from other high-volume units [14,[19][20][21]. Our re-operation rate was 1.3%, but some of the leaks and bleedings could probably have been treated conservatively.…”
Section: Discussionsupporting
confidence: 83%
“…Patient demographics in our study are comparable with other European series on gastric bypass [14,19,20] regarding BMI and co-morbidities. We had a high followup rate (98.6%) on weight loss and early and serious complications.…”
Section: Discussionsupporting
confidence: 81%
“…They develop within the first few days after surgery and can sometimes be devastating if not treated promptly and aggressively, although they may be completely asymptomatic. Marginal In the literature, the incidence of leaks at the GJS after RYGBP varies between extremes of 0% and more than 8%, but usually between 1% and 3% and is reported to depend, among others, on the experience of the surgeon, the surgical approach, the technique of anastomosis (hand sewn versus circular versus linear stapled) and the fact that RYGBP is performed as a primary or re-do procedure [1][2][3][4][5][6][7][8][9][10][11]. Several authors have suggested technical adjuncts to reduce the incidence of leaks, such as reinforcement of the staple line [27], or use of fibrin sealant [28].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31] The timing and extent of postoperative hemorrhage following RYGB and associated clinical symptoms aid in determining management. Overt bleeding and a decline in hematocrit within the first 6 hours post-surgery is an indication that intervention may be required.…”
Section: Postoperative Endoscopy To Detect and Treat Hemorrhagementioning
confidence: 99%